Landscape in situ. The contribution of atmospheres to the understanding of the construction of landscape - Crossey, Nora; Dittel, Julia; Kazig, Rainer; Thiollière, Pascaline; Weber, Florian (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
This paper puts forward a proposal for the consideration of atmospheres within the analysis of the social construction of landscape(s). Starting out from an overview of approaches in constructivist landscape research, focusing on the German speaking world, we may confirm an increased interest in the role of subjective multisensorial experience with regard to constructions of landscape(s), which has, however, not yet been reflected in current research approaches. The concept of atmosphere, with its consideration of multisensorial in situ-encounters, may be able to contribute to the scholarly discussion. Following a presentation of core ideas of the concept of atmosphere(s), we show that, on a conceptual level, the conscious experience of atmospheres and their effects may inform the construction of landscapes. Furthermore, in a methodological section we illustrate on the basis of two exploratory examples, how the influence of atmospheres on subjective constructions of landscape(s) may be empirically accessible. The paper closes with a discussion of our proposal within current trajectories of the Anglophone landscape geography.
Keywords: Landscape; Urban landscape; Atmosphere; Constructivism; Theoretical perspective; Empirical approach